2006
DOI: 10.1007/s00383-006-1681-0
|View full text |Cite
|
Sign up to set email alerts
|

Early scrotal exploration in all cases is the investigation and intervention of choice in the acute paediatric scrotum

Abstract: The acute scrotum in the paediatric population is a clinical dilemma where a definitive diagnosis can only truly be made at surgical exploration. We postulate that surgical exploration in all cases allows truly accurate diagnoses, treats the torted appendage testes and enables the validity of clinical signs associated with scrotal pathology to be assessed. We retrospectively reviewed all boys less than 15 years old who presented to our institution with scrotal pain over a 2 year period. A total of 121 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
74
1
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 17 publications
9
74
1
10
Order By: Relevance
“…Radiological studies, such as CDU and scintigraphy [3,4], have been suggested to be of use in order to spare unnecessary surgery, but no agreement has been reached about the ideal work up of these patients, and some authors still advise surgical exploration in every case [5]. Clinical problems and medico-legal issues are not limited to the preoperative diagnosis of TT.…”
Section: Discussionmentioning
confidence: 99%
“…Radiological studies, such as CDU and scintigraphy [3,4], have been suggested to be of use in order to spare unnecessary surgery, but no agreement has been reached about the ideal work up of these patients, and some authors still advise surgical exploration in every case [5]. Clinical problems and medico-legal issues are not limited to the preoperative diagnosis of TT.…”
Section: Discussionmentioning
confidence: 99%
“…Murphy et al revealed the wisdom of liberal scrotal exploration in all acute scrotum cases. (18) Gunther et al suggested that if Doppler sonography is performed correctly as a standard procedure, it may replace surgical exploration, which would only be indicated in cases of doubt. (1) They suggested that the diagnostic benefit of routine surgical evaluation is small in comparison with the risks of aspiration and wound infection and that total costs may be reduced by replacing surgery with ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that colour Doppler sonography can identify testicular torsion in boys reliably, 5 the surgical exploration remains the gold standard diagnostic tool so as to maximise the chances of testicular salvage in case of testicular torsion. 6 After torsion of the testis and testicular appendix have been excluded, the acute scrotum in paediatric patients is frequently attributed to AE. The exact incidence of AE in the paediatric population is difficult to establish.…”
mentioning
confidence: 99%
“…In different series it ranges from 3.7% to 71% of children presenting with acute scrotum. [1][2][3][4][5][6][7][8] A bimodal age distribution of epididymitis has been reported in many series, with peak incidence in infancy and mainly the age group of 10-12 years. [7][8][9][10] In our district hospital we encountered six consecutive cases of AE in prepubertal boys over a period of two months.…”
mentioning
confidence: 99%